2015
DOI: 10.1073/pnas.1408111112
|View full text |Cite
|
Sign up to set email alerts
|

iASPP, a previously unidentified regulator of desmosomes, prevents arrhythmogenic right ventricular cardiomyopathy (ARVC)-induced sudden death

Abstract: Desmosomes are anchoring junctions that exist in cells that endure physical stress such as cardiac myocytes. The importance of desmosomes in maintaining the homeostasis of the myocardium is underscored by frequent mutations of desmosome components found in human patients and animal models. Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a phenotype caused by mutations in desmosomal components in ∼50% of patients, however, the causes in the remaining 50% of patients still remain unknown. A deficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 62 publications
7
52
0
2
Order By: Relevance
“…Moreover, iASPP did not show the preferential nuclear localization described originally. This is in accordance with previous data showing that iASPP nuclear localization is restricted to specific cell lines, in particular melanoma 24 or undifferentiated epithelial cells 19,33 . In addition our results do not support a model in which iASPP is mostly present in the cytoplasm as an anti-parallel homodimer 24 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, iASPP did not show the preferential nuclear localization described originally. This is in accordance with previous data showing that iASPP nuclear localization is restricted to specific cell lines, in particular melanoma 24 or undifferentiated epithelial cells 19,33 . In addition our results do not support a model in which iASPP is mostly present in the cytoplasm as an anti-parallel homodimer 24 .…”
Section: Discussionsupporting
confidence: 93%
“…While earlier studies focused on the ability of iASPP to inhibit p53 16,18 , more recent work has identified new functions of iASPP, associated with the Pro-rich region. For instance, iASPP interacts with desmine and desmoplakin in cardiomyocytes to sustain desmosome integrity 19 and with the Nrf2 transcription factor regulator Keap1, to promote antioxidative signaling 20 . We report here that iASPP interacts with EB1 via a typical SxIP motif located within the intrinsically disordered region.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, animal models of cardiovascular disease have to be included in the validation process to establish whether or not the accuracy in normal mice presented extrapolates to pathological cases. The technique should particularly be suitable for mouse models of ventricular arrhythmias [39]. All this will be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively spliced versions of the Dsc, PKP, and DP proteins have been described. Other proteins that are associated with desmosomes in a tissue-specific manner include Perp, corneodesmosin, envoplakin, periplakin, kasrin, and the newly identified regulator of desmosomes, inhibitor of apoptosis-stimulating protein of p53 (iASPP; Notari et al 2015).…”
Section: Desmosome Composition and Structurementioning
confidence: 99%